2009
DOI: 10.1111/j.1365-294x.2009.04413.x
|View full text |Cite
|
Sign up to set email alerts
|

Restricted dispersal in a continuously distributed marine species: common bottlenose dolphinsTursiops truncatusin coastal waters of the western North Atlantic

Abstract: The marine environment provides an opportunity to examine population structure in species with high dispersal capabilities and often no obvious barriers to genetic exchange. In coastal waters of the western North Atlantic, common bottlenose dolphins, Tursiops truncatus, are a highly mobile species with a continuous distribution from New York to Florida. We examine if the highly mobile nature coupled with no obvious geographic barriers to movement in this region result in a large panmictic population. Mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
135
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(146 citation statements)
references
References 85 publications
9
135
1
1
Order By: Relevance
“…Genetic analysis also was used to assign the coastal or offshore morphotype (Rosel et al, 2009) for 185 samples from bottlenose dolphins. All other bottlenose dolphins were by default considered the coastal morphotype.…”
Section: North Carolina Geographymentioning
confidence: 99%
“…Genetic analysis also was used to assign the coastal or offshore morphotype (Rosel et al, 2009) for 185 samples from bottlenose dolphins. All other bottlenose dolphins were by default considered the coastal morphotype.…”
Section: North Carolina Geographymentioning
confidence: 99%
“…Recent research has demonstrated that common bottlenose dolphins Tursiops truncatus (hereafter bottlenose dolphins or dolphins) exhibit extensive population structuring, meeting the definition, for management purposes, of stocks as demographically independent populations (Moore & Merrick 2011). Along the US Atlantic coast, Rosel et al (2009) identified at least 5 genetically differentiated coastal and estuarine populations, confirming demographic independence despite the ab sence of hard barriers, such as isolated estuaries. Genetic analyses, coupled with photo-identification (photo-ID) results, have identified structuring of bottle nose dolphin populations over relatively small coastal ranges such as for T. truncatus in Hawaii (Baird et al 2009, Martien et al 2012, Brazil (Fruet et al 2014), South Africa (Natoli et al 2005), Spain (Fernán dez et al 2013), and the Mediterranean Sea (Gaspari et al 2015), as well as for T. australis in southern Australia (CharltonRobb et al 2015).…”
Section: Introductionmentioning
confidence: 71%
“…Genetic analyses, coupled with photo-identification (photo-ID) results, have identified structuring of bottle nose dolphin populations over relatively small coastal ranges such as for T. truncatus in Hawaii (Baird et al 2009, Martien et al 2012, Brazil (Fruet et al 2014), South Africa (Natoli et al 2005), Spain (Fernán dez et al 2013), and the Mediterranean Sea (Gaspari et al 2015), as well as for T. australis in southern Australia (CharltonRobb et al 2015). Further, while estuaries are porous with regard to movements of dolphins, significant genetic differentiation has been shown to occur among bay, sound, or estuarine (BSE) stocks and between BSE and their adjacent coastal stocks (Sellas et al 2005, Möller et al 2007, Rosel et al 2009. Genetics has additionally shown that structuring can occur on a finer scale, with more than 1 population within close proximity of one another within an estuary (Rosel et al 2009, Mirimin et al 2011, Ans mann et al 2012, Richards et al 2013, Fruet et al 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El estrecho contacto estrecho entre poblaciones costeras de delfines mulares con especies estuarinas (tanto de Tursiops truncatus como de Stenella coeruleoalba u otros) en las cuales el virus sea endémico (Duignan et al 1996) puede llevar a la aparición de un brote. La variación geográfica y la cepa asilada en los distintos brotes puede reflejar el movimiento de las especies de delfines y de los virus que las infectan; de hecho, recientemente se ha reportado que el solapamiento estacional de poblaciones costeras y estuarinas de delfines mulares en algunas épocas del año puede favorecer la propagación de la infección (Rosel et al 2009). Igualmente se ha reportado que la densidad poblacional de delfines listados ha sido un factor determinante para el establecimiento de la infección de forma endémica en las costas mediterráneas (Forcada et al 1994); indicando que densidad poblacional alta favorecería la aparición de una epidemia.…”
Section: Distribución Y Epidemiologíaunclassified